Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Prakarya dan Kewirausahaan - JB. Suhatmaji Sunaryo (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Craft and Entrepreneurship Learning or commonly called PKWU lessons is a lesson that provides discussion on a work that is made and entrepreneurship. To be able to understand material about crafts based on local cultural artifacts/objects, a method is needed, namely Project Based Learning (PjBL). This model is used because it involves student activities in learning that function to solve problems in understanding the subject matter. The subjects of this study were 36 students of class 10 IPS 4 SMA Negeri 1 Sedayu. The purpose of research using the Project Based Learning (PjBL) learning model is that students can understand the subject matter, so that student learning outcomes are better. The final result of the research value obtained by students less than 70 is 2.77% or as many as 1 student, students who get scores equal to 70 and less than 80 are 0% or as many as 0 students, then students who get scores of 80 and less than 90 are 61.11% or as many as 22 students, students who get scores equal to 90 to 100 are 36.11% or as many as 13 students. The Project Based Learning (PjBL) teaching method is very appropriate for improving student learning outcomes in class X IPS 4 SMA Negeri 1 Sedayu because the PJBL learning model is very enjoyable for students and later it is hoped that it will enable students to develop entrepreneurial abilities in the field of crafts in the community.